Glycine Metabolism and Oxalacetate Transport by Pea Leaf Mitochondria - Day, David A. (1981)
Isolated pea leaf mitochondria oxidatively decarboxylate added glycine. This decarboxylation could be linked to the respiratory chain (in which case it was coupled to three phosphorylations) or to mitochondrial malate dehydrogenase when oxalacetate was supplied. Decarboxylation rates measured as O(2) uptake, or CO(2) and NH(3) release were adequate to account for whole leaf photorespiration. Oxalacetate-supported glycine decarboxylation, measured by linking malate efflux to added malic enzyme, yielded rates considerably less than the electron transport rates. Butylmalonate inhibited malate efflux but not oxalacetate entry; phthalonate inhibited oxalacetate entry but had little effect on malate or α-ketoglutarate oxidation. It is suggested that oxalacetate and malate transport are catalyzed by separate carrier systems of the mitochondrial membrane.